Experience of conductive hearing loss and impacts of hearing aid use throughout life - Hampton, Thomas; Loureiro, Manuel; Mortimer, Kevin; Nyirenda, Deborah (Frontiers in Rehabilitation Sciences, 2024)
IntroductionHearing loss and Deafness/deafness affects as much as 5% of the world's population and has a considerable health and economic burden. We explored the relationship with hearing and hearing aids as well as other assistive technology for health in general with a cohort of UK adults who have conductive hearing loss. We anticipated that insights could lead to greater understanding for the delivery of assistive technology (AT) for conductive hearing loss and the participant's lived experience related to technology and society.MethodsThis study presents the qualitative findings from a mixed methods study exploring the story of each participant's hearing, the impact on their lives and their experience and use of AT. A purposive sample of 33 adults with conductive hearing loss took part in semi-structured interviews. Participants were aged ≥18 years and had previously attended outpatient ENT or audiology clinic at University Hospitals Sussex NHS Foundation Trust. Transcripts underwent thematic analysis.ResultsThe overarching theme was “A changing relationship over time with deafness, themselves and society”. The three principle sub-themes of the interviews were “a technological world” describing the necessity of interaction with people & technology' both as children and adults, then the concept of “Normalised Marginalisation”-the struggle of childhood and school in the face of social norms' and typicality. Finally, there were issues raised about visibility and “the visible display of D/deafness”, tied to aesthetics, vanity and traditional ideas about masculinity. Many participants described their adoption of new technology or devices as “transforming their life” and their quality of life without assistive technology as significantly impaired.ConclusionInsights from this study described the experiences of adults with conductive hearing loss and the ways in which they have a difficult relationship with their deafness, including how they felt and viewed themselves and how they interacted with society, particularly as children and young adults. The potential for benefit of assistive technology for hearing health was deemed by many participants to be a necessary bridge integrating them in relationships with other people in society. Early notions of disability, typicality and social norms frequently persisted into adulthood and these insights should be considered by all those professional seeking to provided hearing health assistance to individuals with conductive hearing loss.